Analysis of racial variations in disease characteristics, treatment patterns, and outcomes of patients with chronic lymphocytic leukemia. Issue 7 (24th April 2016) - Nabhan, Chadi; Chaffee, Kari G.; Slager, Susan L.; Galanina, Natalie; Achenbach, Sara J.; Schwager, Susan M.; Kay, Neil E.; Shanafelt, Tait D.
Abstract : The impact of race on outcomes of patients with chronic lymphocytic leukemia (CLL), the most common leukemia in the west, is not well studied. We aimed to understand racial variations in clinical and disease characteristics, treatment patterns, and outcomes in patients with CLL. We utilized the Mayo Clinic CLL database to perform an analysis of these characteristics and natural history of non‐white (NW) compared to white (W) CLL patients. Differences by race in median overall survival (OS) and time‐to‐first‐treatment (TTFT) were investigated. Of the 4215 CLL patients, 4114 (97.6%) were W and 101 (2.4%) were NW. NW patients were younger (median age at diagnosis 59.4 vs . 63.4; P  = 0.003) and more likely to have an elevated LDH (28.0% vs . 16.2%; P  = 0.02). No differences in prognostic parameters were noted. No major differences were observed in treatment selection. OS and TTFT were similar between both groups. In the largest analysis of NW‐CLL patients in North America, and contrary to historical retrospective reports, W and NW patients appear to have comparable outcomes when treated similarly. These findings suggest previously noted outcome differences may be due to disparities in access to care and management rather than differences in disease biology. Am. J. Hematol. 91:677–680, 2016. © 2016 Wiley Periodicals, Inc.